The use of angiogenic and antiangiogenic factors in the differential diagnosis of pre-eclampsia, antiphospholipid syndrome nephropathy and lupus nephritis. (October 2014) - de Jesus, GR; de Jesus, NR; Levy, RA; Klumb, EM
Pre-eclampsia (PE) is a major cause of maternal mortality and morbidity, perinatal deaths, preterm birth and intrauterine growth restriction. Differential diagnosis with antiphospholipid syndrome (APS) nephropathy and systemic lupus erythematosus (SLE) nephritis during pregnancy is difficult, if not sometimes impossible, as all three diseases may present hypertension and proteinuria. Improvement in diagnosis of PE has also offered new paths for differential diagnosis with other conditions and the analysis of angiogenic (vascular endothelial growth factor, placental growth factor) and antiangiogenic factors (serum soluble fms-like tyrosine kinase 1, soluble endoglin) is promising for differentiation between PE, APS nephropathy and SLE nephritis. This article reviews published studies about those factors in non-pregnant and pregnant patients with APS and SLE, comparing with patterns described in PE.